(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
A solvent-assisted approach was established to make CH3NH3PbI3 perovskite absorber layers. A mixture of CH3NH3I, PbI2, c-butyrolactone, and dimethyl sulfoxide (DMSO) was used, followed by the addition of chlorobenzene (CB). The approach produced ultra-flat and dense perovskite capping layers atop mesoporous films TiO2, allowing for a significant boost in the performance of carbon electrode-form perovskite solar cells using free whole transport material (HTM) (PSCs). As a comparative solvent, toluene (TO) was also investigated. The generated HTM-free PSCs form on drop-casting CB showed a power conversion efficiency (PCE) of 9.73 percent at an annealing temperature of 100 C, which is 36 and 71 percent greater than those fabricated from perovskite films using TO or without adding an additional solvent, respectively. The interaction between the intermediate phase of PbI2–DMSO–CH3NH3I and the extra solvent was discussed. The effect of annealing temperature on absorber film development, morphology, and crystalline structure was also examined, and the results were connected with photovoltaic performance. Highly efficient, simple, and stable HTM-free solar cells with a PCE of 11.44 percent were created using the best perovskite absorbers annealed at 120 C.